The Urban Organization of the Socio-Spatial Environment in Towns of the Irkutsk Region - Druzhinina, Inna (project baikal, 2015)
The article observes the problems of formation of socio-spatial environment of new cities of the Irkutsk region in the period of pioneer development of Siberia in the XX century, and the impact of this environment on the modern living conditions. Identification of the key features and main factors affecting the development of new cities and the definition of the specificity of the socio-spatial environment of residential units of Bratsk, Angarsk, Shelekhov and Sayansk cities are presented.